Urgensi Pedagogik Futuristik Dalam Membangun Generasi Emas Indonesia Menghadapi Global Megatrend 2045 - Sukaesih Sukaesih; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Global trends including technological advances, social and economic changes require a rapid response from the education system. The year 2045 brings undeniable challenges in terms of global transformation. The aim of this research is to analyze the important role of futuristic pedagogy in overcoming various challenges in 21st century learning to build Indonesia's future golden generation in facing the global megatrend of 2045. This research uses a literature study method to explore the urgency of futuristic pedagogy in shaping the future golden generation Indonesia in facing the 2045 global megatrend. In facing the challenges of the 2045 global megatrend, a futuristic pedagogical approach is crucial for the world of Indonesian education. The integration of technology in learning, the development of 21st century skills, project and simulation-based learning, and differentiated and personalized learning help prepare young people to face the complex dynamics of the future. The teacher's role is key in facilitating the use of technology as an effective learning tool, while encouraging students to develop a deep understanding of an ever-evolving world.